2019
DOI: 10.1002/jor.24523
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Plasticity in Musculoskeletal Development, Regeneration, and Disease

Abstract: In this review, we highlight themes from a recent workshop focused on “Plasticity of Cell Fate in Musculoskeletal Tissues” held at the Orthopaedic Research Society's 2019 annual meeting. Experts in the field provided examples of mesenchymal cell plasticity during normal musculoskeletal development, regeneration, and disease. A thorough understanding of the biology underpinning mesenchymal cell plasticity may offer a roadmap for promoting regeneration while attenuating pathologic differentiation. © 2019 Orthopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 110 publications
(268 reference statements)
1
8
0
Order By: Relevance
“…This has been enabled in part by modern genetic labeling of cells for fate mapping. Our work and others has now clearly demonstrated that chondrocytes give rise to the new bone during repair of fractures in appendicular and facial bones (Bahney et al 2019;Kaji et al 2020;Wong et al 2021). Chondrocytes also contribute to the osteoblast lineage during long bone development.…”
Section: Models Of Endochondral Ossificationsupporting
confidence: 64%
See 1 more Smart Citation
“…This has been enabled in part by modern genetic labeling of cells for fate mapping. Our work and others has now clearly demonstrated that chondrocytes give rise to the new bone during repair of fractures in appendicular and facial bones (Bahney et al 2019;Kaji et al 2020;Wong et al 2021). Chondrocytes also contribute to the osteoblast lineage during long bone development.…”
Section: Models Of Endochondral Ossificationsupporting
confidence: 64%
“…The concept gained popularity in the 1800s, was based on histological and anatomical observations, and is often discussed in terms of pathological changes in tissue in response to environmental insult such as with Barrett’s esophagus (Zhang et al 2021) or in the context of cancer as reviewed (Giroux and Rustgi 2017). However, recent evidence suggests that metaplasia and cellular plasticity contribute to development and regeneration within the musculoskeletal system and beyond (Kaji et al 2020; Brown et al 2022; Goldenring and Mills 2022). Metaplasia appears to be common in normal and pathologic processes in multicellular organisms.…”
Section: Paligenosis: a Process Of Metaplasia In Multicellular Organismsmentioning
confidence: 99%
“…Their switch to another lineage can occur through transdifferentiation (transition from one to another differentiated cell type) or through dedifferentiation (reversal to a progenitor state) followed by redifferentiation (into a different cell type) (1). While enforceable experimentally in many cells (e.g., induction of pluripotent stem cells), it has been documented to this date in only a discrete number of events in vivo (e.g., epithelial-to-mesenchymal transition, cancer, and heterotopic ossification) (2)(3)(4). Thorough evaluation of cellular plasticity prevalence and underpinnings are prerequisites to understanding normal and disease processes and eventually tailor efficient disease treatments.…”
mentioning
confidence: 99%
“…Importantly, in vitro results cannot be directly translated to in vivo situation. Notably, in vivo studies using mouse models proposed that HO precursors could originate from skeletal muscle endothelial, “mesenchymal” or pericyte populations or tendon and connective tissue cells or even circulating stem/precursor cells [ 1 , 5 , 21 , 137 ]. Some initial studies suggested that endothelial cells, characterized by the presence of TIE2, which is the tyrosine kinase receptor for angiopoetin, are engaged in HO formation [ 138 , 139 ].…”
Section: Heterotopic Ossification Precursor Cellsmentioning
confidence: 99%
“…In human, however, such cells are not precisely described yet. Moreover, it is also suggested that different types of cells could be responsible for HO development dependently of HO type [ 1 , 5 , 21 , 137 ].…”
Section: Heterotopic Ossification Precursor Cellsmentioning
confidence: 99%